2021
DOI: 10.26508/lsa.202101180
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune anti-DNA and anti-phosphatidylserine antibodies predict development of severe COVID-19

Abstract: High levels of autoimmune antibodies are observed in COVID-19 patients but their specific contribution to disease severity and clinical manifestations remains poorly understood. We performed a retrospective study of 115 COVID-19 hospitalized patients with different degrees of severity to analyze the generation of autoimmune antibodies to common antigens: a lysate of erythrocytes, the lipid phosphatidylserine (PS) and DNA. High levels of IgG autoantibodies against erythrocyte lysates were observed in a large pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
(66 reference statements)
1
12
0
3
Order By: Relevance
“…Thus, the presence of anti-DNA and anti-PS autoantibodies may play an important role in the pathogenesis of COVID-19 and could be sought as a predictive biomarker for disease severity and specific clinical manifestations. Another study also correlated the presence of autoantibodies against the lung protective protein Annessin-A2 with the mortality of COVID-19 patients [ 352 , 353 ]. The innate immune response is non-specific, because it is not influenced by previous exposure to other pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the presence of anti-DNA and anti-PS autoantibodies may play an important role in the pathogenesis of COVID-19 and could be sought as a predictive biomarker for disease severity and specific clinical manifestations. Another study also correlated the presence of autoantibodies against the lung protective protein Annessin-A2 with the mortality of COVID-19 patients [ 352 , 353 ]. The innate immune response is non-specific, because it is not influenced by previous exposure to other pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to malaria, high levels of circulating autoantibodies have been reported in COVID-19 patients, but surprisingly, circulating immune complexes were not increased in these patients. The autoantibodies include similar targets to malaria, such as PS and dsDNA ( 51 ), but also expand to newer targets such Annexin A2 ( 52 ), that have not been studied in malaria patients. The autoantibody repertoire seems to be broad during COVID-19 and is not clear if it’s selected preferably against any autoantigen although their pathogenic role has been highly suggested by multiple studies ( 53 , 54 ).…”
Section: Lessons From Malaria Applied To Covid-19 and Other Infectionsmentioning
confidence: 99%
“…Thus, from an immunological point of view, the immune reaction in response to SARS-CoV-2 infections shares similarities to autoimmune diseases. In this context it was reported that COVID-19 patients carrying antinuclear antibodies (ANAs), antiphospholipid antibodies or anti-SS-A/Ro show more severe COVID-19 courses than patients devoid of these autoantibodies [7][8][9][10]. Interestingly, in non-symptomatic COVID-19 patients and patients with only mild disease courses, an age-dependent tendency towards the development of autoantibodies such as anti-cyclic citrullinated peptides (CCP)-IgG and anti-tissue transglutaminase (TTG)-IgA antibodies was also detected [11].…”
Section: Introductionmentioning
confidence: 99%